Investigating Students’ Needs in English for Specific Purposes: A Study at Universitas Timika - Nurmaisyah Nurmaisyah; Achmad Yani; Iskandar Iskandar (Journal of English Language Teaching, Literature and Culture, 2025)
Timika Regency, located in Central Papua, Indonesia, hosts a rich tapestry of ethnic communities, notably the indigenous Amungme and Kamoro groups. Despite supportive government initiatives like scholarships aimed at advancing education, delivering impactful English language instruction to non-specialist students poses ongoing difficulties. In higher education settings, English courses adopt an English for Specific Purposes (ESP) framework, customizing content to align with students' chosen fields of study. This research explores the ESP learning requirements of Communication Science undergraduates at Timika University, with the goal of guiding the creation of an effective Semester Learning Plan (SLP). Employing a descriptive quantitative methodology, the study gathered insights via structured questionnaires distributed to students, faculty members, and key stakeholders. Results reveal a strong demand for English resources and competencies that directly support academic pursuits and future careers, underscoring the value of ESP tailored to specific disciplines. The analysis stresses the importance of adapting ESP programs to regional educational realities. Moving forward, scholars should investigate the sustained effects of such ESP strategies on enhancing students' preparedness for both scholarly achievements and professional success.